If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13Y + -12X + 14Z = 12Y + 14Z + 48X Reorder the terms: -12X + 13Y + 14Z = 12Y + 14Z + 48X Reorder the terms: -12X + 13Y + 14Z = 48X + 12Y + 14Z Add '-14Z' to each side of the equation. -12X + 13Y + 14Z + -14Z = 48X + 12Y + 14Z + -14Z Combine like terms: 14Z + -14Z = 0 -12X + 13Y + 0 = 48X + 12Y + 14Z + -14Z -12X + 13Y = 48X + 12Y + 14Z + -14Z Combine like terms: 14Z + -14Z = 0 -12X + 13Y = 48X + 12Y + 0 -12X + 13Y = 48X + 12Y Solving -12X + 13Y = 48X + 12Y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-48X' to each side of the equation. -12X + -48X + 13Y = 48X + -48X + 12Y Combine like terms: -12X + -48X = -60X -60X + 13Y = 48X + -48X + 12Y Combine like terms: 48X + -48X = 0 -60X + 13Y = 0 + 12Y -60X + 13Y = 12Y Add '-13Y' to each side of the equation. -60X + 13Y + -13Y = 12Y + -13Y Combine like terms: 13Y + -13Y = 0 -60X + 0 = 12Y + -13Y -60X = 12Y + -13Y Combine like terms: 12Y + -13Y = -1Y -60X = -1Y Divide each side by '-60'. X = 0.01666666667Y Simplifying X = 0.01666666667Y
| -5x+2y+z= | | 5x+2y-z= | | 15x^2+10x-9=0 | | 2(5)=16-(-6) | | -49=2x+3x+6 | | X+7=14X+7-7 | | 145-342=2 | | 6x+7-7x=3 | | -10x=-4+2x | | 8=2(2c-5)c | | 13z+9=8-3z+2 | | 2x=(1/50) | | 12q=6 | | 6v^2-100=10v | | 3ln(2x+8)=14 | | 10p-7+2-1=3+5 | | 1/11 | | 2/7=x/100 | | 40x-9=71 | | 3t+10=4t+5 | | -7y+7-6=-14y+6-4 | | (-8.946)(14.08)= | | 5x+8=41 | | equals= | | X^3+7x^2=x^2+16x | | n=3/4 | | (X^3)+(3x^2)-8x=0 | | y=(3/5*-2)-2/3 | | y=3/5×-2-2/3 | | 9x-7=6-4+5 | | (-12/47)(-47/24)= | | (-12/47)(-47/12)k= |